Relationship between Self Disclosure and Bullying of Social Media User High School Students - Yanita Putri Rahmadhani; Firman Firman (Counseling and Humanities Review, 2021)
This research is motivated by students who bully at school as a result of excessive self-disclosure on social media. This study aims to: (1) describe self-disclosure on social media, (2) describe student bullying, and (3) examine the relationship of self-disclosure with high school students using social media. The research approach uses a quantitative approach with a descriptive correlational type. The population of the study was students of SMA Negeri 1 Luhak Nan Duo using proportional random sampling technique. Data were collected through self-disclosure questionnaires and student bullying. Furthermore, the data were analyzed using descriptive statistics with percentage techniques, and for normality test, linearity test and the relationship between the two variables used statistical analysis with the Pearson Product Moment technique with the help of SPSS version 20.0 for windows. Based on the research, it was found: (1) students 'self-disclosure was in the high category, (2) students' bullying was in the medium category and (3) there was a relationship between self-disclosure and bullying of high school students using social media. The implication in guidance and counseling services is that guidance and counseling teachers provide services to students related to bullying and self-disclosure problems on social media.